Ultra-poor Graduation Endline Survey in Somalia, 2024 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset comes from the endline survey of a randomized impact evaluation of the Ultra-Poor Graduation (UPG) Model implemented by World Vision Somalia in internally displaced persons (IDP) camps in Baidoa, Somalia. The UPG program supports extremely vulnerable households through a combination of cash transfers, savings groups, productive asset or skills training, and life-skills coaching. The endline survey, conducted from September 27 to October 20, 2024, collected follow-up data to assess final program outcomes on food security, household consumption, and asset accumulation, as well as financial inclusion, income generation, social cohesion, and locus of control.